Cultivation of Salix L. - A Potential Bio-energy Crop in the Kashmir Himalaya, India - Andleeb, Lubna; Munshi, A.H; Dar, A.R (Current Botany, 2013)
Salix is considered to be a golden crop among the tree canopy and Salix cultivation is known to be a practicable concept to get the best possible return in yield and profit. The eventual aim of present scientific activity was to produce maximum biomass/hectare of different Salix species/cultivars in the Kashmir Valley for resource oriented activities. The seventeen accessions of various Salix species/cultivars were identified from different aggregates and cultivated under Short Rotation Coppice (SRC) method in natural as well as controlled conditions for three consecutive years. Various growth attributes of different Salix species/cultivars which were taken into consideration for the present study includes, the size of the leaves (length as well as breadth), number of branches per cutting, length of the branches and the number of leaves per branch.Salix babylonica showed the maximum (8cm, 11cm, 15cm) leaf length in first, second and third year of cultivation respectively, while minimum values for same was recorded for Salix pycnostachya. The number of branches per cutting also showed an increase in biomass in all the species/cultivars during the three years of cultivation. Salix babylonica showed the maximum length of branches in the first two years while Salix viminalis recorded the maximum in the last year. Salix babylonica depicted the highest number of leaves per branch during the three years of the experiment. During the three years of cultivation of different Salix species/cultivars, all the seventeen accessions showed an increase in biomass in all the attributes.